Statistical Analysis of Pi2 Pulsations Observed by Van Allen Probes. Issue 9 (14th September 2022) - Takahashi, Kazue; Lysak, Robert; Vellante, Massimo
Abstract: The relative importance of propagating and cavity mode waves remains an important question regarding the generation of Pi2 pulsations detected on the ground. To determine the wave mode, we statistically generate spatial maps of magnetospheric oscillations that are coherent with ground Pi2 pulsations. The magnetospheric observations were made by the two Van Allen Probes spacecraft over a 7‐year period. The amount and quality of the spacecraft data allow us to investigate the mode structure of Pi2 pulsation in ways that were not possible in previous studies. We use the H component of low‐latitude ground Pi2 pulsations detected in the 22–02 magnetic local time (MLT) sector as the reference signal to generate L ‐MLT and meridional maps of the coherence, amplitude, and phase of the magnetospheric electric and magnetic field components defined in magnetic field aligned coordinates. We identify low‐frequency and high‐frequency components in Pi2 power spectra, and we are able to determine the mode structure of the high‐frequency events for the first time. The maps demonstrate that the poloidal components have higher coherence than the toroidal components. For each frequency component, the maps of the poloidal components agree with those of cavity mode oscillations obtained in a numerical simulation using realistic models for the magnetospheric mass density and magnetic field. This result is conclusive evidence of the cavity mode nature of Pi2 pulsations detected in the inner magnetosphere. Plain Language Summary: The magnetospheric phenomena known as Pi2 pulsations are oscillations of the electric and magnetic fields with periods around 1 min. The pulsations typically occur at the onset of nightside disturbances known as substorms, which result in sudden brightening of auroras. Pi2 pulsations propagate globally and are detected on the ground even at noon, serving as a useful monitor of substorms. This is analogous to propagation of seismic waves generated by earthquakes. Similar to the solid Earth, the magnetosphere sustains both propagating waves and normal mode oscillations (cavity modes), with the latter exhibiting discrete frequencies and standing wave structures that depend on the plasma distribution in the magnetosphere. There is debate on whether Pi2 pulsations are propagating waves or cavity modes. We construct spatial maps of the amplitude and phase of magnetospheric Pi2 pulsations using observations made by the Van Allen Probes spacecraft. The maps show theoretically predicted mode structures of cavity modes. Key Points: Van Allen Probes data are used to generate maps of the amplitude and phase of Pi2 pulsations in the inner magnetosphere A secondary frequency component of the pulsations is treated separately from the main component The maps for both frequency components show radial structures of cavity mode resonances